FINANCIAL PERFORMANCE ANALYSIS BASED ON GOVERNMENT FINANCIAL STATEMENTS (Study on The Goverment of Kabupaten Blitar) - HENDRA AGUS PRASTYA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The purpose of this study is to determine the financial performance of Kabupaten Blitar. Financial ratios analysis used to measure the level of financial autonomy, effectiveness in realization of regional revenue, financial efficiency of expenditures, the harmony of local government to prioritize the allocation of expenditure and DSCR to see the government's ability to pay debts. The sample is Kabupaten Blitar. The analyzed data is Laporan Realisasi APBD in 2012-2014. The Goverment of Kabupaten Blitar is expected to improve its revenue by optimizing resources and expanding sectors that potentially could increase revenue, so the dependency from the central government could be decreasing. The Goverment of Kabupaten Blitar is also expected to be more proportionate in allocating their expenditure by reducing operational expenditure and increasing capital expenditure.